Comparison of peak ground reaction force, joint kinetics and kinematics, and muscle activity between a flexible and steel barbell during the back squat exercise - Hutchison, R. E.; Caterisano, A. (Journal of Human Kinetics, 2019)
The flexible barbell is purported to improve training gains compared with an Olympic steel barbell (SB) during the back squat exercise with Division I collegiate American football programs. The two bars loaded at 30% 1-repetition maximum were compared with ten trained Division I American football players (n = 10; age = 19.5 years; body mass = 89.4 kg; body height = 182.0 cm) completing 10 repetitions of the back squat exercise. Analysis included integrated-peak values of electromyography of the rectus femoris, biceps femoris, rectus abdominis, erector spinae, external oblique, vastus lateralis, ground reaction forces, and joint kinematics and kinetics of the hip, knee, and ankle. The flexible bar elicited significant increases in peak joint kinetics (Hip Moment: 229 ± 54 Nm vs. 209 ± 52 Nm; Hip Power: 494 ± 151 W vs. 382 ± 134 W; Knee Power: 305 ± 108 W vs. 241 ± 63 W), peak vertical ground reaction forces (1195 ± 209 N vs. 1120 ± 203 N), and muscle activity (Vastus Lateralis: 75.7 vs. 66.5%, Rectus Abdominis: 190 vs. 115%, Rectus Femoris: 69.8 vs. 59.9%, External Oblique: 115 vs. 69.0%). Greater vertical ground reaction forces, hip moment, hip power, knee power, and muscle activity of the vastus lateralis, rectus abdominis, rectus femoris, and external oblique suggest the FB provides biomechanical and physiological mechanisms for training gains over the SB for 30% of 1-repetition maximum loads.